Attitudes towards the death penalty: An assessment of individual and country-level differences - McCarthy, Daniel (European journal of criminology, 2024)
Research on public attitudes to the death penalty has been predominantly understood through single nation-states, especially within the USA. Examinations of international differences in citizens? support for the death penalty have been scarce, particularly among continents with a high volume of retentionist nations (e.g. Asia). In this paper, we draw on a dataset of 135,000 people from across 81 nations to examine differences in death penalty support. We find that residents of retentionist nations are generally more supportive of the death penalty than those from abolitionist nations. But this general difference masks important differences both within and between countries. At the country-level, residents of abolitionist nations with autocratic political systems and those with higher homicide levels were more likely to support the death penalty than residents of other abolitionist nations. At the individual level, greater support for a strong dictatorial-type leader and perceptions of political corruption are associated with increased support for the death penalty, but only in abolitionist nations. By contrast, more frequent religious worship, perceived egalitarianism in a nation, and support for the political performance of government reduced death penalty support in abolitionist nations but increased support in retentionist nations, while belief in individual responsibility and critical views towards ethnic minorities increased support for the death penalty across both abolitionist and retentionist nations.